Residence program on Medical Physics at Hospital das Clínicas of São Paulo University - Rodrigues, Laura N.; Furnari, Laura; da Silva, Marco A.; Rubo, Rodrigo A.; dos Santos, Gabriela R.; Menegussi, Gisela (Revista Brasileira de Física Médica, 2015)
The main goal of the Residence Program on Medical Physics at Clinicas Hospital is to provide a specialization course of 24 months. The candidate selection is made in 2 steps: a general examination with 50 questions of multiple choices and a specific examination which does not presuppose the candidates must have certain knowledge in the area. After this second written exam, an interview is promoted in order to evaluate other aspects not covered by the previous exams, including some ethical issues, the ability to deal with patients and the multidisciplinary aspect among other professionals in the hospital. The Board Committee also evaluates the candidates’ curriculum according to rules established by the Residence Coordination (participation in scientific meetings, trainings performed during graduation in Radiotherapy and scientific publications). The residence is thus directed to students which concluded bachelor’s degree or a degree in Physics, and aims to train professionals skilled in Radiotherapy area, including the obtaining of further qualified professional title offered by the Brazilian Association of Medical Physics. The students attend lectures, seminars and the routine of the hospital. They also perform experimental work and develop a monograph to be presented at the end of the residence’s period. In the last 5 years, almost 50 candidates have been attending to the selective process for only 2 available positions per year; the candidates come from different parts of the country, including students from the North, Northeast, Central-West, South and Southeast regions. It should be noticed in the last 5 years that most of the approved candidates are students coming from Graduation on Medical Physics, especially in the São Paulo state. For the last 10 residents, 20% were hired by companies in the Radiotherapy area; the remaining residents were hired by hospitals, 20% have found jobs in the Northeast region and 60% in São Paulo state.